Atlas of Prenatal Hair Follicle Morphogenesis Using the Pig as a Model System - Jiang, Yao; Zou, Quan; Liu, Bo; Li, Shujuan; Wang, Yi; Liu, Tianlong; Ding, Xiangdong (Frontiers in Cell and Developmental Biology, 2021)
The pig is an increasingly popular biomedical model, but only a few in depth exist on its studies in hair follicle (HF) morphogenesis and development. Hence the objective of this study was to identify the suitability of the pig as an animal model for human hair research. We performed a classification of pig HF morphogenesis stages and hair types. All four different hair types sampled from 17 different body parts in pig were similar to those of humans. The Guard_2 sub-type was more similar to type Ⅱ human scalp hair while Guard_1, Awl, Auchene and Zigzag were similar to type Ⅰ scalp hair. Based on morphological observation and marker gene expression of HF at 11 different embryonic days and six postnatal days, we classified pig HF morphogenesis development from E41 to P45 into three main periods—Induction (E37-E41), Organogenesis (E41-E85) and Cytodifferentiation (>E85). Furthermore, we demonstrated that humans and pigs share high similarities in HF morphogenesis occurrence time (early/mid gestational) and marker genes expression patterns. Our findings will facilitate the study of human follicle morphogenesis and research on complex hair diseases and offer researchers a suitable model for human hair research.